Spillovers from US monetary shocks: Role of policy drivers and cyclical conditions - Elif C. Arbatli-Saxegaard; Davide Furceri; Pablo Gonzalez Dominguez; Jonathan David Ostry; Shanaka Jayanath Peiris (Asian Development Bank Institute (ADBI), 2022)
We provide new evidence on the spillover effects from US interest rate changes, focusing on factors that are pertinent to the current conjuncture: weak recovery prospects in emerging market and developing economies (EMDEs), and the confluence of macroeconomic shocks shaping the path of interest rates in the US. The drivers of US monetary policy matter for the nature of spillovers. With an SVAR-IV model used to identify structural monetary policy, demand, and supply shocks, we find that an increase in US interest rates driven by demand shocks engenders a positive spillover to economic activity in the near term, while an exogenous tightening of monetary policy would have a large negative spillover effect. Spillovers from US monetary policy shocks also depend on the state of the business cycle, exerting larger effects when growth is weak outside the US. Finally, tighter US monetary policy affects the left tail of the growth distribution disproportionately: the fat left tail highlights the salience of growth at risk.
Keywords: F4; E5; C3; 330; US monetary policy; foreign spillovers